FAKTOR PENYEBAB MASYARAKAT SUKU SUNDA MENIKAHKAN ANAK PEREMPUANNYA PADA USIA DINI (13-16 Thn) - Juniati, Resti - (Pendidikan Sosiologi, 2014)
Statutory marriage chapter 7 No. 1 of 1974, explained that if a man has reached the age of 19 years and the woman has reached the age of 16 years is allowed to hold marriage. But in reality there are still many teenagers who get married at an early age, especially teenagers who come from the Sundanese community located in the village of Tanjung Benuang. This study aimed to describe the causal factors Sundanese community her children tend to marry at an early age.This study uses a social definition paradigm with social action theory proposed by Max Weber, by using a qualitative approach with descriptive type. Informants of this research were taken by purposive sampling with the informant criteria: Sundanese community of parents who marry off their daughters at an early age, the brother of the father of teenage girls are married at an early after, and brother of adolescent girls are married at an early age. The type of data in this study is in the form of primary data and secondary data. The data collection techniques in this study in the form of in-depth interviews, observation, and study document. Unit of data analyst in this research that individuals Sundanese communities who marry off their daughters at an early age in the village of Tanjung Benuang. The data analysis performed in this study are: One, noted that generate field notes, second, to collect and sort out, classify and create the index, and the third, to think that the data has the meaning of the data categories.The study found that the factors causing the Sundanese community tends marry off their daughters at an early age, namely: first, the educational background of parents, second parents work background, third, experience of parental background.